Patient experiences and health system responsiveness among older adults in South Africa - Karl Peltzer; Nancy Phaswana-Mafuya (Taylor & Francis Group, 2012)
Background: As populations age, health systems must adapt and develop approaches that meet the needs of older patients with increasing multiple chronic conditions. Understanding older populations’ perceptions of quality of care is critical to developing measures to increase the utilization of primary healthcare services. Using the data from the Global Study on Ageing and Adult Health (SAGE) survey, the current study aims to evaluate the degree of perceived responsiveness with outpatient and inpatient healthcare in South Africa. Methods: We conducted a national population-based cross-sectional study with a sample of 3,840 individuals aged 50 years or older in South Africa in 2008. The questionnaire included sociodemographic characteristics, healthcare utilization and responsiveness, and other health variables. Results: Healthcare utilization was 9% inpatient care in the past 3 years and 50% outpatient care in the past 12 months. The overall mean perceived responsiveness score for inpatient care was 71 and for outpatient care 69. According to the evaluation of inpatient care, autonomy and prompt attention showed the lowest while quality, confidentiality, and dignity showed the highest degree of perceived responsiveness among all the areas analyzed. Regarding outpatient care, prompt attention showed the lowest while quality, confidentiality, and dignity the highest degree of perceived responsiveness scores. Overall, perceived healthcare responsiveness was higher in private than in public inpatient and outpatient healthcare facilities. Multivariate analysis found that being from the White population group (OR=3.96, CI=1.54–19.19), not a public health facility (OR=0.34, CI=0.17–0.69), poor subjective health status (OR=0.53, CI=0.38–0.75) and having health insurance paying for the outpatient care visit (OR=3.39, CI=1.24–9.27) were associated with outpatient perceived healthcare responsiveness, whereas male gender (OR=0.36, CI=0.14–0.89), 80 years or older (OR=5.83, CI=1.11–30.63), being from the Indian or Asian population group (OR=8.97, CI=1.14–70.35) and not residing in a rural area (OR=0.28, CI=0.10–0.80) were associated with inpatient perceived healthcare responsiveness. Conclusion: Prompt attention, autonomy, communication and access were identified as priority areas for actions to improve responsiveness of healthcare services in South Africa.